(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The socio-economic changes taking place in our country create new opportunities for reforming education on the basis of humanity, which requires the efforts of the whole society. Today, a person who is flexible, dynamic, able to live and work in new, constantly changing conditions, who not only perfectly knows his profession, but also a developing person is in demand in our society. At the same time, it is necessary to take into account that modern civilization cannot be realized without relying on morally oriented intellect. Intellectual, spiritual and professional development of a person and self-development, including to students studying in the "Technological Machines and Equipment" bachelor’s course of study at the faculty of "Engineering Technologies" at a higher educational institution (HEI) is done continuously.